TURKISM IN THE THOUGHT OF DR. RIZA NUR: A READING FROM THE PERSPECTİVE OF PRIMORDIALISM - Ergüç, Veysel (My University, 2021)
Turkism was one of the political movements emerging in the last period of the Ottoman Empire. Under scope of the Turkism movement, initially Ottoman belonging and realism were identifying factors. Subject matter realism comprises of such concepts like balance, strategy and interest. In the subsequent period, matter of racial origins became prevalent within framework of Turkism movement. Racial origin was construed as descending from Turkic blood. The thinker who combined two veins in the Turkism movement was Dr. Rıza Nur. In this article, including both veins in the Turkism movement, Dr. Rıza Nur's understanding of Turkism will be examined. Dr. Rıza Nur's thought will be read in connection with the primordialsm, which is one of the theories of nationalism.